1987
DOI: 10.1128/aac.31.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of analogs of guanine and guanosine against American Trypanosoma and Leishmania spp

Abstract: The growth inhibitory effects of six guanine and guanosine analogs, 3-deazaguanine (compound 1); 3-deazaguanosine (compound 2); 6-aminoallopurinol (compound 3); 9-I-xylofuranosyl guanine (compound 4); a ribosylated derivative of compound 3, 6-aminopyrazolo(3,4-d)pyrimidin-4-one (compound 5); and 5-aminoformycin B (compound 6), were tested against some pathogenic members of the family of American Trypanosomatidae. Compounds 1 and 2 were highly active against Trypanosoma cruzi, Trypanosoma rangeli, and American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Even though various nucleoside and nucleobase analogues display good activity in vitro and/or in vivo (e.g. [41–45]) only the pyrimidine antifolate pyrimethamine is widely used clinically, particularly in combination with sulphadoxine against malaria [46], and also against toxoplasmosis [47,48]. In addition the purine nucleobase allopurinol is used in combinations against leishmaniasis [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Even though various nucleoside and nucleobase analogues display good activity in vitro and/or in vivo (e.g. [41–45]) only the pyrimidine antifolate pyrimethamine is widely used clinically, particularly in combination with sulphadoxine against malaria [46], and also against toxoplasmosis [47,48]. In addition the purine nucleobase allopurinol is used in combinations against leishmaniasis [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…The antitrypanosomals considered on this study are representatives of families with diverse structural patterns. [29][30][31][32][33][34][35][36][37][38] Figure 2 shows the whole active set collected from the literature for this work. The selected inactive group included antivirals, sedative/hypnotics, diuretics, anticonvulsivants, hemostatics, oral hypoglycemics, antihypertensives, antihelminthics, anticancer compounds as well as some other kinds of drugs, guaranteeing at the same time a great structural variability.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Leishmania glycolipids (Avila et al 1991) could induce both anti-carbohydrate IgE and IgG antibodies, as demonstrated in schistosomiasis (van der Kleij et al 1999). At present, we do not know the biological role played by these anti-carbohydrate IgG and IgE antibodies in the host-Leishmania relationship nor the factors influencing their production.…”
Section: Discussionmentioning
confidence: 99%